2022
DOI: 10.1186/s12933-022-01582-w
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the GRACE score by the triglyceride glucose index improves the prediction of clinical outcomes in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Background The Global Registry of Acute Coronary Events (GRACE) score derived from clinical parameters at the time of hospital discharge is a powerful predictor of long-term mortality and reinfarction after acute coronary syndrome (ACS). The triglyceride glucose (TyG) index, which is a simple and reliable surrogate marker of insulin resistance, has been demonstrated to be an independent predictor of long-term adverse major adverse cardiac events, irrespective of diabetes mellitus. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…A recent large-scale prospective study suggested that the TyG index is an independent predictor for the progression of coronary artery calcification, especially in individuals without heavy coronary artery calcification at baseline [7]. Moreover, an increased TyG index has been shown to be independently associated with higher risks of atherosclerotic cardiovascular diseases, including myocardial infarction [8], and worse prognosis in patients with ACS, irrespective of diabetes mellitus [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent large-scale prospective study suggested that the TyG index is an independent predictor for the progression of coronary artery calcification, especially in individuals without heavy coronary artery calcification at baseline [7]. Moreover, an increased TyG index has been shown to be independently associated with higher risks of atherosclerotic cardiovascular diseases, including myocardial infarction [8], and worse prognosis in patients with ACS, irrespective of diabetes mellitus [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients were grouped by the optima cut-off value of 8.72 for the TyG index with an AUROC of 0.621, similar to previous studies in which the TyG had an AUROC of 0.644 and 0.607 for the prediction value, respectively [ 29 , 30 ]. There were also studies using the tertiles.…”
Section: Discussionmentioning
confidence: 93%
“…Neglia et al also reported that the TyG index was a strong independent predictor of adverse CV events in patients with chronic coronary syndrome (CCS) [39]. Moreover, the TyG index has been shown to be a good predictor of clinical outcomes in patients with ACS [21,22,32,33,[40][41][42][43]. Luo et al revealed that STEMI patients with a higher TyG index were at a greater risk of adverse CV events after PCI, and this correlation persisted even after adjusting for confounders [22].…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, they also demonstrated that there was a signi cant association between MACCE and TyG index in NSTE-ACS patients undergoing elective PCI without diabetes, with a median follow-up of 4 years [33]. According to Xiong and his research team, the TyG index was shown to be an independent risk factor for the primary endpoint among patients with ACS after PCI, which consisted of all-cause mortality and nonfatal MI [40]. In addition, Zhang et al included only LDL-C < 1.8 mmol/L and nondiabetic patients with ACS to reduce the confounding impacts of hyperlipidemia and diabetes on adverse CV events, and found that a higher TyG index was still associated with a higher incidence of acute myocardial infarction (AMI), a larger infarct size and a higher rate of subsequent revascularization [41].…”
Section: Discussionmentioning
confidence: 99%